Influence of Environment Aging on the Thermal Insulation of Sustainable Ecofriendly Composites - Ramanaiah, K.; Palla, Hari Sankar; Satya Mohan, Kunapuli Siva (Journal of Composites and Biodegradable Polymers, 2025)
In recent years, researchers are increasingly emphasized the development of sustainable biodegradable composites to minimize environmental impact and broaden their potential in engineering fields. This study investigates the influence of environmental aging including, exposer to tap water, sea water and aqueous (NaOH) solutions, on the thermal insulation behavior of sansevieria /PLA-based biodegradable composites. The water uptake characteristics and diffusion coefficients were determined and analyzed to understand their effects on material performance. Results revealed a significant rise in thermal conductivity after moisture absorption, indicating a decline in insulation performance. the percentage increase in thermal conductivity of S4 in tap water, sea water and aqueous solution compared to dry state are 112.69, 156.03 and 189.36, respectively. The mechanisms responsible for the deterioration of thermal insulation due to water penetration are examined, providing insights in to the durability and environmental stability of these insulation materials.